PEMANFAATAN LIMBAH KULIT PISANG MENJADI SABUN CUCI PIRING DENGAN BAHAN ADITIF KULIT JERUK - Darajat, Zakiyah; Septiani, Mimin; Fitria, Fitria (Universitas Methodist Indonesia, 2023)
Banana production in Bontang City has increased every year. Along with the high productivity of bananas, the amount of banana peel waste will also increase. In general, waste in the form of banana peels is only used as animal feed or disposed of without further processing so that it can cause environmental pollution. For this reason, it is necessary to manage banana peels so that they have a higher economic value. Banana peel contains alkaloids, flavonoids, phenols, tannins and saponins. This Saponin will produce foam so that it can be used as a washing agent and can also be used as a kitchen equipment cleaner. The samples in this activity were ripe banana peels and orange peels as additives (fragrances and essential oil producers). The method used in the Activities for the Community is the presentation of the material. Discussion, and practice of making dish soap. Participants were very enthusiastic in participating in a series of training activities for making dish soap. The result of this training is an environmentally friendly dish soap product according to the method provided.